2009
DOI: 10.1089/neu.2008.0538
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Preconditioning Attenuates Early Apoptosis after Spinal Cord Ischemia in Rats

Abstract: This study tested the hypothesis that spinal cord ischemic tolerance induced by hyperbaric oxygen preconditioning (HBO-PC) is mediated by inhibition of early apoptosis. Male Sprague-Dawley rats were preconditioned with consecutive 4 cycles of 1-h HBO exposures (2.5 atmospheres absolute [ATA], 100% O(2)) at a 12-h interval. At 24 h after the last HBO pretreatment, rats underwent 9 min of spinal cord ischemia induced by occlusion of the descending thoracic aorta in combination with systemic hypotension (40 mmHg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 48 publications
3
45
0
1
Order By: Relevance
“…The evidence is clear that VEGF is anti-apoptotic agent and enhanced angiogenesis 24 . HBOT promotes tissue preservation with reduced apoptosis because it diminishes the levels of superoxide and hydrogen peroxide, resulting in a subsequent reduction in the amount of cytochrome c in the cytosol 25 . Indeed, Nylander et al 26 have observed improved mitochondrial function associated with…”
Section: Studies Of In Vitro Ischemiamentioning
confidence: 99%
“…The evidence is clear that VEGF is anti-apoptotic agent and enhanced angiogenesis 24 . HBOT promotes tissue preservation with reduced apoptosis because it diminishes the levels of superoxide and hydrogen peroxide, resulting in a subsequent reduction in the amount of cytochrome c in the cytosol 25 . Indeed, Nylander et al 26 have observed improved mitochondrial function associated with…”
Section: Studies Of In Vitro Ischemiamentioning
confidence: 99%
“…This does not mean that the tissues are equal: the method of histological evaluation with hematoxylin-eosin can show necrosis, hemorrhage, hypermia, degeneration of nervous substances (cystic degeneration) and cell infiltration that had not changed with hyperbaric oxygen therapy, but the result could be different if we had used other techniques of neurochemical assays to access activities of antioxidant enzymes, like Mn-superoxide dismutase and catalase dosage and expression of antiapoptotic protein in the mitochondria, which are more sensitive methods to differ tissues with ischemic degeneration. 6,24 Supplementation with biological and cell resources should constitute the next steps to be taken, and may explain the difference in performance of the experimental groups that we have seen here. Maybe a study with antioxidant enzymes in different postoperative moments (days 7, 14, 21 and 28) could help to explain the absence of a significant difference in the functional analysis on day 7.…”
Section: Discussionmentioning
confidence: 95%
“…Formalin-fixed, paraffin-embedded (FFPE) tissues (n = 58, ages [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were sectioned at 5 mm, transferred onto Fisher Superfrost Plus slides, deparaffinized, rehydrated and then subjected to antigen retrieval using Vector Antigen Unmasking Solution, pH 6.0 (Vector Laboratories) for 1 h at 80°C. The sections were incubated in a humidity chamber overnight at 4°C with a mouse monoclonal antibody developed against 4HNE-modified low-density lipoprotein (clone NA59) that binds to lysine adducts of 4HNE.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] Of special relevance to carcinogenesis are adaptive responses to chronic oxidative stress identified that might lead to the evolution of subpopulations of cells that can evade mechanisms that limit the propagation of cells with oxidatively-damaged DNA, notably, increased resistance to apoptosis [28][29][30][31] and tolerance to DNA damage. [32][33][34] The chronic oxidative stress final-common-path hypothesis, referred to above, is based on the following considerations.…”
Section: Do Not Distributementioning
confidence: 99%